Peningkatan Hasil Belajar Matematika Materi FPBKPK Melalui Metode Pembelajaran Think Pair Share (TPS) pada Siswa Sekolah Dasar - Siti Syamsiah (Jurnal Pendidikan Dasar, 2019)
The purpose of this study was to determine the increase in mathematics learning outcomes of FPB-CPD material through the application of learning methods Think Pair Share to class IVB SD Negeri Kleco II No. 242 Surakarta Academic Year 2018/2019. The form of this research is classroom action research (CAR) which is carried out in two cycles. Each cycle consists of four stages, namely planning, implementation, observation, and reflection stages. The subjects of this study were teachers and fourth grade students of SD Negeri Kleco II No. 242 Surakarta 2018/2019 school year, totaling 29 students. Data collection techniques used were observation, interviews, tests, and documentation. The data validity used was source triangulation and technical triangulation. Analysis of the data used is interactive analysis. The results of this study can be concluded that through the learning method Think Pair Share can improve the mathematics learning outcomes of FPB-KPK material in class IVB of semester I SDN Kleco II Surakarta in the academic year 2018/2019. Keywords: Mathematics learning outcomes, FPB-KPK, Think Pair Share